Bombers of World War II - Robinson Masters, Nancy; Air Force Museum (U.S.) (Mankato, Minn : Capstone High/Low Books, 1998)
Introduces the different kinds of bombers used during World War II, their capabilities, the kinds of missions on which they were sent, and any special characteristics.
Includes bibliographical references (p. 44) and index.
4.8
5-8
Keywords: Bombers -- United States -- History -- Juvenile literature; World War, 1939-1945 -- Aerial operations, American; Bombers; Airplanes, Military; World War, 1939-1945 -- Aerial operations; Bombers; Military airplanes; World War, 1939-1945 -- Aerial operations